Composition and Antibacterial Activity of the Essential Oil from the Rhizome of Turmeric (Curcuma longa L.) - Naz, Shagufta; Ilyas, Saiqa; Jabeen, Safia; Parveen, Zahida (Asian Journal of Chemistry, 2010)
The essential oil from the rhizome of turmeric (Curcuma longa L. Bannu var.) grown in Pakistan was isolated by the hydro-distillation. Chemical constituents of the essential oil were separated and identified by means of gas chromatography/mass spectrometry (GC-MS). The chromatographic analysis of oil showed 17 constituents of which, 5 chemical constituents contributing 80 % of the total oil constituents could be identified. The main components of the essential oil were ar-turmerone (38.59 %), turmerone (8.88 %), curlone (12.9 %). eucalyptol (1.59 %) and caryophyllene (0.99 %) are the minor class of essential oil. Therefore, in the volatile oil from rhizomes of turmeric, sesquiterpenoids are major compounds, accounting for 46 %. The antibacterial activity of Bannu oil was also evaluated against four pathogenic bacterial strains (Bacillus subtilis, B. macerans, B. licheniformis and Azotobacter sp.) using agar well diffusion method. Ethanol, hexane and ethyl acetate extracts exhibited antibacterial activity as indicated by minimum inhibitory concentration (MIC) values, but other extracts of butanol and water did not exhibit any antibacterial activity. Ethanolic extract is most active against tested microorganisms. The MIC values of different strains and extracts ranged from 0.01-1.0 mm in diameter.